Pengaruh Keterbukaan Diri di Media Sosial Terhadap Insecurity pada Mahasiswa Universitas ‘Aisyiyah Yogyakarta - Aulia Ahmad; Ratna Yunita Setiyani Subardjo (EduInovasi: Journal of Basic Educational Studies, 2024)
This research aims to find out whether there is an influence of self-disclosure in the media on students' feelings of insecurity. Self-disclosure on social media, such as providing personal information, achievements, or feelings, makes students more vulnerable to social comparisons, criticism, and negative comments. This research uses a descriptive and inferential quantitative approach with a simple regression analysis method. The subjects of this research were 'Aisyiyah Yogyakarta University students who actively use social media with a sample of 96 people. Data was collected through an online survey via Google Forms which measured self-disclosure on social media and feelings of insecurity and distributed via social media. Data were analyzed using classic assumption tests and hypothesis testing in the form of simple regression analysis. The research results show that there is a very significant influence between self-disclosure on social media on insecurity in students. This is shown by the regression coefficient value of 3751.630, which indicates that the higher the self-disclosure on social media, the greater the possibility of students feeling insecure or lacking self-confidence. This research still has shortcomings, such as subjects that are not balanced between genders, does not focus on one social media, and research subjects are still limited, therefore it is hoped that future research can improve the findings.